Agricultural Water Use and Management in Arid and Semi-arid Areas: Current Situation and Measures for Improvement - Dehghannisanij, Hossein; Oweis, Theib; Qureshi, Sarwar (Annals of Arid Zone, 2016)
Water is rapidly becoming scarcer especially in arid and semi-arid areas such as Central West Asia and North Africa Region (CW ANA), while irrigated agriculture is critical for national and world food security in these regions. Due to large gaps between crop demands and rainfall, most/countries of these regions cannot have productive form of agriculture without 'assured irrigation supplies. Continuous decrease in the surface water resources has put enormous pressure on groundwater resources and as a result; throughout, the regions groundwater tables are declining. Since water is the most limited factor- in these regions, improving the productivity of existing water resources is an attractive alternative to sustain irrigated agriculture. Therefore, there is a strong need to educate farmers to shift their thinking from "maximizing crop' yields" to "optimizing crop yields". This paper reviews the current situation of water scarcity, agricultunll water productivity, and suggests options for sustainable management of land and water resources in these regions. The results of this study showed that substantial and sustainable improvements in water productivity can be achieved through integrated management of farm-resources. On-farm irrigation water management techniques such as deficit irrigation, if coupled with better cropping patterns together with appfopriate cultural practices, and improved genetic make-up, will help to achieve this objective. Conventional water-management and cropping pattern guidelines, designed to maximize yield per unit area, need to be revised for achieving maximum water productivity. The wide ranges recorded in crop water productivities suggest that agricultural production can be maintained to its current level by using 20 to 40% less water if new efficient water management . practices are adopted.